2021
DOI: 10.1111/iej.13466
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and efficiency of guided root‐end resection using a dynamic navigation system: a human cadaver study

Abstract: Aim To determine and compare the accuracy and efficiency of a dynamic navigation system (DNS) with a freehand (FH) technique when conducting root-end resection in a human cadaver model. Methodology Forty roots in cadaver heads were included and divided into two groups: DNS (n = 20) and FH (n = 20). Cone beam computed tomography (CBCT) scans of all teeth were taken. The drilling path and depth were planned virtually to using the Xguide software (X-Nav Technologies, Lansdale, PA, USA). Osteotomy and root-end res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
0
28
0
3
Order By: Relevance
“…19 One study was ex vivo, conducted in human teeth in a fresh cadaver head for endodontic microsurgery. 18 Most of the previous studies included here were single evaluations of the DNS. 5,9,10,[15][16][17]19,21,26 The majority of the comparison studies compared DNS and the FH technique, 7,8,[11][12][13][14]18,20 in which the robot's accuracy and precision are expected to be higher than a human surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 One study was ex vivo, conducted in human teeth in a fresh cadaver head for endodontic microsurgery. 18 Most of the previous studies included here were single evaluations of the DNS. 5,9,10,[15][16][17]19,21,26 The majority of the comparison studies compared DNS and the FH technique, 7,8,[11][12][13][14]18,20 in which the robot's accuracy and precision are expected to be higher than a human surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…5 Since then, the DNS's potential has been explored for different applications in endodontics. Currently, the DNS has been considered for conventional and minimally invasive access cavities, [5][6][7][8][9][10][11][12] locating calcified canals, [13][14][15][16] endodontic microsurgery, [16][17][18] post removal, 19,20 and intraosseous anesthesia anesthesia. The DNS is an emerging technology that can revolutionize endodontics by accurately and safely delivering minimally invasive procedures and avoiding catastrophic mishaps during complex procedures.…”
Section: Videomentioning
confidence: 99%
“…Targeted endodontic microsurgery has since continued to develop and has since improved with the consolidation of the necessary digital workflows (Ray et al, 2020), the detailed assessment of anatomy specific to guided surgical techniques, such as the location of the greater palatine artery (Smith et al, 2021), and the validation of the techniques by larger case series (Buniag et al, 2021; Figure 48). Another variation of guided surgical techniques is dynamic navigation, a freehand approach to endodontic microsurgery without templates or guides that is directed by CBCT location and calibrated surgical burs and instruments tracked by a stereoscopic vision camera (Dianat et al, 2021; Gambarini et al, 2019). All these options provide clinicians with previously unknown precision and safety nets during surgical procedures.…”
Section: Future Directions—recent Advancementsmentioning
confidence: 99%
“…Such guided approach, despite the lack of sufficient scientific evidence to be recommended routinely outside of a research setting, showed promising results, in the light of the principles of the microsurgical endodontics. Another approach that was based on three‐dimensional digital planning and guided execution is surgical endodontics using a dynamic navigation system which provide real‐time visualization on patient's CBCT images of the procedure, thus allowing for superior accuracy (and consequently less invasive) than using a freehand technique (Dianat et al, 2021; Gambarini et al, 2019). The digitally driven techniques aimed at reducing the influence of operator's ability and the so‐called “technique effect” whilst performing the surgery, potentially minimizing the risk of avoidable mistakes during the procedure.…”
Section: Reviewmentioning
confidence: 99%